Amplification of TruSeq ancient DNA libraries with AccuPrime Pfx: consequences on nucleotide misincorporation and methylation patterns. Issue 1 (3rd June 2015) - Seguin-Orlando, Andaine; Hoover, Cindi A.; Vasiliev, Sergei K.; Ovodov, Nikolai D.; Shapiro, Beth; Cooper, Alan; Rubin, Edward M.; Willerslev, Eske; Orlando, Ludovic
<x content-type="archive" xml:space="preserve">Abstract</x> Recent developments in high-throughput sequencing (HTS) technologies have enabled the reconstruction of complete genome sequence and nucleosome and methylation maps from ancient individuals. A diversity of degradation reactions affect DNA molecules after an organism dies, introducing specific nucleotide misincorporation patterns in HTS data that are typically exploited to distinguish modern contaminants and authentic DNA templates. In this study, we used two different DNA polymerases to amplify Illumina TruSeq DNA libraries built on DNA extracts from ancient equines. The AmpliTaq Gold, widely used in ancient DNA studies, generated amplified libraries showing typical misincorporation patterns. Such patterns were partially lost following AccuPrime Pfx amplification, for which a two-fold reduction of endogenous content was also observed. This is explained by the inability of the AccuPrime Pfx to bypass uracils, which represent the most common post-mortem base modification and derive from the post-mortem deamination of cytosines. Our study, therefore, reveals that amplification of TruSeq DNA libraries with AccuPrime Pfx increases the cost of whole-genome sequencing for samples showing substantial levels of DNA degradation and creates atypical nucleotide misincorporation patterns for data authentication. The method can, however, be exploited to identify ancient methylation marks, and potentially, nucleosome occupancy maps. Statement of significance After an organism dies, DNA molecules are subjected to degradation resulting in fragmentation and bases modifications. After high- throughput sequencing (HTS), it is possible to detect the molecular signature of these damages, demonstrating that the data generated is authentic. DNA extracts from fossil remains indeed contain, besides endogenous ancient molecules, a variety of modern contaminants, but only the former generally exhibits molecular signatures typical of post-mortem damage. Our study reveals that these signatures depend on the protocol used for amplifying DNA samples. It thus helps defining better guidelines for authenticating ancient HTS data. Our results also reveal one molecular approach that limits our ability to exploit the whole complexity of ancient DNA molecules preserved in fossil specimens but can help track ancient methylation marks. Data availability The authors confirm that all data underlying the findings are fully available without restriction. All relevant data are contained within the paper.